2009
DOI: 10.1093/jac/dkp392
|View full text |Cite
|
Sign up to set email alerts
|

Cationic phosphorodiamidate morpholino oligomers efficiently prevent growth of Escherichia coli in vitro and in vivo

Abstract: Cationic PMOs inhibited bacterial growth in vitro and in vivo, and Gux-PMOs were more effective than Pip-PMOs. However, neither was as effective as the equivalent PMO-peptide conjugates. Subcutaneous treatment showed that 5 + Gux-AcpP or (RXR)(4)XB-AcpP entered the circulatory system, reduced infection and increased survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
1
48
0
1
Order By: Relevance
“…This combination of chemical and biological methods allows the killing of drug resistant bacteria and of bacteria in which the gene for gyrase A is targeted at concentrations of conjugate at least tenfold lower than previously used (13). Others have also attacked bacterial drug resistance in a similar manner (7)(8)(9) without the seemingly practical success now reported here for bacterial cells in liquid culture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of chemical and biological methods allows the killing of drug resistant bacteria and of bacteria in which the gene for gyrase A is targeted at concentrations of conjugate at least tenfold lower than previously used (13). Others have also attacked bacterial drug resistance in a similar manner (7)(8)(9) without the seemingly practical success now reported here for bacterial cells in liquid culture.…”
mentioning
confidence: 99%
“…Among these are the use of basic peptide-morpholino oligonucleotide conjugates. Some practical success has been observed, in particular, in terms of curing mice infected with bacteria and prevention of infection of mammalian tissue by dangerous viruses (4)(5)(6)(7)(8)(9). A previously undescribed basic peptide (cell-penetrating peptide: CPP), derived from a protein found in human T cells, Tyr-AlaArg-Val-Arg-Arg-Arg-Gly-Pro-Arg-Gly-Tyr-Ala-Arg-Val-Arg-ArgArg-Gly-Pro-Arg-Arg, which has no biological activity on its own (10), has been employed to make a previously undescribed conjugate with phosphorodiamidate morpholino oligonucleotides (PMOs) by the chemical method described by Abes et al (11).…”
mentioning
confidence: 99%
“…Validated essential genes among different bacterial species include fbpA/ fbpB/fbpC (Harth & et al, 2002(Harth & et al, , 2007 and glnA1 (Harth & et al, 2000) in Mycobacterium tuberculosis, gyrA/ompA in Klebsiella pneumonia (Kurupati & et al, 2007), inhA in Mycobacterium smegmatis (Kulyte & et al, 2005), oxyR/ahpC in Mycobacterium avium (Shimizu & et al, 2003), NPT/EhErd2 in Entamoeba histolytica (Stock & et al, 2000(Stock & et al, , 2001, gtfB in Streptococcus mutans (Guo & et al, 2006), fmhB/ gyrA/hmrB (Nekhotiaeva & et al, 2004a) and fabI (Ji & et al, 2004) in Staphylococcus aureus, 23S rRNA (Xue-Wen & et al, 2007), 16S rRNA plus lacZ/bla (Good & Nielsen, 1998), and RNAse P (Gruegelsiepe & et al, 2006) in Escherichia coli, and acpP in Burkholderia cepacia (Greenberg & et al, 2010), Escherichia coli (Deere & et al, 2005b;Geller & et al, 2003aGeller & et al, , 2003bGeller & et al, , 2005Mellbye & et al, 2009Mellbye & et al, , 2010Tan & et al, 2005;Tilley & et al, 2007) as well as Salmonella enterica serovar Typhimurium (Mitev & et al, 2009;Tilley & et al, 2006). Mellbye et al, First proof-of-principle evidence was given by White et al in 1997 for successful increasing the bactericidal activity of norfloxacin by antisense inhibiting the marRAB operon in Escherichia coli (White & et al, 1997).…”
Section: Validated Targets In Bacteria 22221 Targeting Essential mentioning
confidence: 99%
“…It has been shown that PNA or Morpholino antisense oligomers in conjugation with (KFF)3K, (RX)6B-, (RXR)4XB-, and (RFR)4XB peptides are able to eliminate bacterial infection in mice [18,[24][25][26]. Furthermore, it is also possible that the peptides which efficiently transport PNA oligomers in mammalian cells may also be capable of transporting PNA oligomers in bacteria [27,28].…”
mentioning
confidence: 99%